2016
DOI: 10.1080/03602532.2016.1179754
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic disposition and biological significance of simple phenols of dietary origin: hydroxytyrosol and tyrosol

Abstract: Hydroxytyrosol and tyrosol are dietary phenolic compounds present in virgin olive oil and wine. Both compounds are also endogenously synthesized in our body as byproducts of dopamine and tyramine metabolisms, respectively. Over the last decades, research into hydroxytyrosol and tyrosol has experienced an increasing interest due to the role that these compounds may play in the prevention of certain pathologies (e.g. cardiovascular, metabolic, neurodegenerative diseases and cancer). The translation of promising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
144
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(149 citation statements)
references
References 118 publications
4
144
0
1
Order By: Relevance
“…Despite the promising anticancer activity of HT, there have been concerns about its poor bioavailability owing to its extensive metabolism (38). It has been suggested that the conjugated forms of HT should also be included in the cytotoxic assays, along with free HT, because this alone would be truly reflective for the HT in biological systems (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the promising anticancer activity of HT, there have been concerns about its poor bioavailability owing to its extensive metabolism (38). It has been suggested that the conjugated forms of HT should also be included in the cytotoxic assays, along with free HT, because this alone would be truly reflective for the HT in biological systems (38).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the conjugated forms of HT should also be included in the cytotoxic assays, along with free HT, because this alone would be truly reflective for the HT in biological systems (38). On a positive note, it was noted that HT is a ‘safe’ compound and can be administered at higher doses without signs of any genotoxic or mutagenic effects (38; 39). Recently, there has been an interest in synthesis of HT-derivatives with a focus on improving the overall efficacy (40).…”
Section: Discussionmentioning
confidence: 99%
“…A high concentration of tyrosol at about 25 mM caused the complete inhibition of ATP synthase. Tyrosol is primarily found in extra virgin olive oil, but it is also synthesized endogenously by humans [63]. Tyramine, which is derived from the amino acid tyrosine, can undergo a metabolic pathway in humans leading to the formation of tyrosol [64].…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of HT have been demonstrated in human, cellular and animal models, mainly consumed as EVOO [17,23] The HT from EVOO has also shown to increase insulin sensitivity and the secretory capacity of β-pancreatic cells, thus reducing the risk of developing metabolic syndrome. The phenolic content of olive oil depends on the place of cultivation, climate, variety of the olive, and its level of ripening at the time of harvest, reaching levels of 100–600 mg/kg, and approximately 50% of that phenolic content corresponds to HT and its derivatives [24,25]. HT is also present in wine, and it is considered a secondary metabolite of tyrosine formed by yeasts during alcoholic fermentation, having an approximate concentration up to 5 mg/L [26].…”
Section: General Characteristics Of Hydroxytyrosolmentioning
confidence: 99%
“…HT is also present in wine, and it is considered a secondary metabolite of tyrosine formed by yeasts during alcoholic fermentation, having an approximate concentration up to 5 mg/L [26]. In humans, there is an endogenous formation of HT from dopamine, which is favored in the presence of ethanol [24]. De la Torre et al, 2006 compared short-term and postprandial effects of moderate doses of EVOO (1.7 mg HT) and wine (0.35 mg HT), and found that the urinary recovery of HT was greater from wine intake than from EVOO consumption, despite having a lower HT content, which is explained by the endogenous formation from dopamine favored by the alcohol content of the wine [27].…”
Section: General Characteristics Of Hydroxytyrosolmentioning
confidence: 99%